Chemistry teachers’ pedagogical content knowledge: A review of empirical research published in SSCI Journals from 1986 to 2024 - Deng, Feng; Zhang, Lifan; Zhu, Junhao; Dou, Bingxin; Lan, Wanrong (Teaching and teacher education, 2025)
Pedagigical Content Knowledge (PCK) has been a seminal framework in research on teaching and teacher education. Searching in Web of Science, we reviewed 82 articles to address the two research questions—how PCK is conceptualized and how it is assessed in empirical chemistry education research. Findings show general agreement on PCK as a bridge between content and pedagogy. However, variation exists in the inclusion of other components, reflecting differing theoretical models. Qualitative methods dominate, with limited use of quantitative tools or standardized rubrics. Research is geographically concentrated. Emerging trends include increased focus on topic specificity, integration of pre- and in-service teacher perspectives, and growing application of the Consensus Model and Refined Consensus Model (RCM). The review highlights a need for methodological innovation, including the development of comprehensive evaluation tools and greater use of technology to support PCK research. These findings inform future directions in theory, methodology and pedagogy. •Provides a comprehensive review of 82 empirical studies on chemistry PCK.•Explores how PCK is conceptualized in empirical chemistry education research.•Analyzes methods used for investigating PCK in chemistry teaching contexts.•Highlights key themes in the conceptualization and measurement of PCK.